Reformator seti zemlya-voda i nauchnogo obrazovania - Т. Aitmatov (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
This article describes the biography of T. Aitmatova, Soviet government, land and water reform, issues of strengthening Soviet power and spiritual features of the people.
Keywords: Tsarist empire, Soviet power, land and water reform, education, Jadidism movement